Hybrid Decoding for Polar Codes - Choi, Soyeon; Yoo, Hoyoung (2018 International SoC Design Conference (ISOCC), 2018)
Among various polar decoding algorithms, SC-List [2] and SC-Flip [3] suffer from high hardware complexity and long decoding latency, respectively. In this paper, a novel hybrid decoding algorithm is proposed to achieve affordable hardware complexity with a suitable decoding latency. According to the experimental results, the proposed method affords a comparable error-correcting performance to that of SC-List [2] and SC-Flip [3] counter parts.